Language Style in the Story Pacman by Viastro on Tumblr - Ananda Fauziah; Lidiyatul Izzah (Scripta : English Department Journal, 2022)
Abstract. This research aimed to analyze about a story entitled pacman by viastro on tumblr social media, which tried to find out the kinds of language style are mostly used in pacman story on tumblr. This research focused on Martin Joos theory which discussed about language style. There are frozen style, formal style, consultative style, casual style, and intimate style. This study was conducted using a descriptive qualitative method in which the data was collected by reading the whole story then finding out the conversation that contains language style. Later on, the researcher classified them based on the types of language style that were found on the conversation, then finding the dominant type of language style. After conducting the analysis, this study showed that there were three types of language style from five types of language style according Martin Joos. They were consultative, casual, and intimate style. Casual was found as the most dominant types of language style in the story with 10 data, intimate with 6 data, and consultative 2 data. Finally, the reseacher hopes that this study will be useful for the future improvement of studying literature, especially about language style.